Implementation Of War Fund Schemes During The First World War In The Madras Presidency (Journal of Pharmaceutical Negative Results, 2021)
The intensification of war demands in 1917 introduced many firsts in India's financial history. Government announced the ‘gift’ of 100 million pounds towards Britain’s war expenses and launched the first of two Indian War Loans to meet this sum on that year. This cast the colonial regime in the role of debtor to a subject population over which it had to reproduce its standing and authority. War loan propaganda could never be too strident, lest Indians conclude that Britain was bankrupt and losing the war. Peasants viewed the war loan as just another oppressive exaction. However, in appealing to the figure of the ‘small investor’, war loan propaganda opened up a space for the conversation with the people from Indian middle classes. During those process, it added fuel to the demand for home rule.